Air Annealing Process for Threshold Voltage Tuning of MoTe2 FET - Soojin Kim; Yeeun Roh; Younguk Choi; Ah Hyun Jun; Hojun Seo; Byeong-Kwon Ju (Applied Sciences, 2022)
A stable doping technique for modifying the conduction behaviour of two-dimensional (2D) nanomaterial-based transistors is imperative for applications based on low-power complementary oxide thin-film transistors. Achieving an ambipolar feature with a controlled threshold voltage in both the p- and n-regimes is crucial for applying MoTe2-based devices as electronic devices because their native doping states are unipolar. In this study, a simple method to tune the threshold voltage of MoTe2 field-effect transistors (FETs) was investigated in order to realise an enhancement-mode MoTe2 thin-film transistor by implementing a facile method to modulate the carrier polarity based on the oxidative properties of MoTe2 FETs. Annealing in air induced a continuous p-doping effect in the devices without significant electrical degradation. Through a precise control of the duration and temperature of the post-annealing process, the tailoring technique induces hole doping, which results in a remarkable shift in transfer characteristics, thus leading to a charge neutrality point of the devices at zero gate bias. This study demonstrates the considerable potential of air heating as a reliable and economical post-processing method for precisely modifying the threshold voltage and further controlling the doping states of MoTe2-based FETs for use in logic inverters with 2D semiconductors.